2014
DOI: 10.1186/s13046-014-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein serves as a prognostic indicator in oral squamous cell carcinoma

Abstract: BackgroundIn our previous study, parathyroid hormone-like hormone (PTHLH) which encodes parathyroid hormone-related protein (PTHrP) was revealed to be up-regulated in oral squamous cell carcinoma (OSCC) compared with paired apparently normal surgical margins using microarray method. However, the function and prognostic indicators of PTHLH/PTHrP in OSCC remain obscure.MethodsThe mRNA levels of PTHLH and its protein levels were investigated in 9 OSCC cell lines and in 36 paired OSCC specimens by real-time PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
(59 reference statements)
3
20
0
Order By: Relevance
“…Both RUNX2 and PTHLH may play certain roles in tumor cell transformation, growth, metastasis, hypercalcemia, and cachexia2829. PTHLH has been reported as a poor prognosis marker of HNSCC1230, however, the role of PTHLH in HNSCC progression is unclear. In this study, we investigated the role of PTHLH in head and neck cancer by analyzing its expression in clinical patients and its phenotypic impact by investigating in vitro and in vivo cell growth due to PTHLH in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both RUNX2 and PTHLH may play certain roles in tumor cell transformation, growth, metastasis, hypercalcemia, and cachexia2829. PTHLH has been reported as a poor prognosis marker of HNSCC1230, however, the role of PTHLH in HNSCC progression is unclear. In this study, we investigated the role of PTHLH in head and neck cancer by analyzing its expression in clinical patients and its phenotypic impact by investigating in vitro and in vivo cell growth due to PTHLH in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…PTHLH promotes cell proliferation, migration, and invasion, and prevents apoptosis in different types of cancers91011. In HNSCC, PTHLH has been reported as a poor prognostic marker and is stimulated in vitro cell growth through promoting cell cycle progression12. However, the regulation mechanism and tumor progression role of PTHLH in HNSCC remains uncertain.…”
mentioning
confidence: 99%
“…In the present study, we found that ICC cells produced PTHLH ligands that respond via the expression of cognate receptors PTH1R, resulting in the continuous activation of downstream signaling pathways. Extensive evidence suggest that PTHLH is viewed as a cellular cytokine, particularly in epithelial cancer cells, that exhibits an autocrine or paracrine role in both cell growth and differentiation [ 26 , 27 ]. In our previous study, we found that overexpression of the PTHLH (LV-PTHLH), which transfects lentivirus-mediated PTHLH GFP without deleting endogenous PTHLH expression in ICC cells, may enter into the non-proliferative cells (data not show).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of IL‐11 to tumor progression and metastasis has been described in other cancers, such as bladder cancer and renal carcinoma . Likewise, PTHrP expressed in OSCCs and other malignant tumors seems to stimulate the activity of osteoclasts, acting both in osteoclastic and osteoblastic cells; moreover, it is related to increased tumor cell proliferation, survival, adhesion, migration and invasion, and is considered an indicator of the prognosis . Related to this, the present study showed that SCC9 cells expressed the IL‐11 and PTHrP genes, which is in agreement with previous reports .…”
Section: Discussionmentioning
confidence: 99%